Effects of dietary olive leaves on performance, carcass traits, meat stability and antioxidant status of fattening Mahabadi male kids. (July 2019) - Jabalbarezi Hukerdi, Y.; Fathi Nasri, M.H.; Rashidi, L.; Ganjkhanlou, M.; Emami, A.
Abstract: Twenty-four Mahabadi goat kids (5–6 months of age) were used to evaluate the effects of feeding olive leaves (OL) on performance, carcass traits and antioxidant status. The kids received three dietary treatments for 84 d with three levels of OL: 0 (control), 7.5 (OL7.5) and 15 (OL15) % (DM basis). Supplementation with OL had no effects on kid performance ( P > 0.05). Total antioxidant capacity (TAC) was increased and malondialdehyde (MDA) concentration was decreased in plasma blood ( P < 0.01) and Longissimus lumborum (LL) muscle (days 1, 4, 7 and 10) of kids ( P < 0.01) with increasing level of OL in diet. The activity of glutathione peroxidase (GSH-Px) in LL muscle was increased ( P < 0.05) in OL15 fed kids compared with control group. Also, glucose content of serum was decreased by adding OL to kid diets ( P < 0.01). Finally, inclusion of OL to kid diets resulted in similar growth performance compared to alfalfa feeding, and improved the antioxidative potential of LL muscle. Highlights: Olive leaf (OL) fed to kids and the antioxidant status was evaluated. OL inclusion in diet had no adverse effects on kid's performance and carcass traits. OL improved total antioxidant capacity (TAC) in meat, blood and liver of kids. Meat lipid oxidation was reduced by OL adding to diet. OL as a cheap by-product can be used instead of conventional forages in kid feeding.